Business process management : 16th International Conference, BPM 2018, Sydney, NSW, Australia, September 9-14, 2018, Proceedings /: 16th International Conference, BPM 2018, Sydney, NSW, Australia, September 9-14, 2018, Proceedings. (2018) - Unknown
No abstract available